Attitudes towards prevention of cervical cancer and early diagnosis among female academicians - FIŞKIN, GAMZE (My University, 2022)
Background It is important for public health to determine the awareness of cervical cancer, which is preventable and treatable when detected at an early stage. Aim This study was conducted to determine female academicians\" attitudes towards prevention and early diagnosis of cervical cancer and the factors affecting them. Methods This descriptive study was conducted with 211 female academicians working in all departments of a university. In the study, the data were collected using questionnaire form, the attitude scale for early diagnosis of cervical cancer, and the attitudes towards prevention of cervical cancer scale. Results It was determined that 68.2% of the female academicians had knowledge about the pap smear test; however, 41.0% of them did not have the test because they could not find time, and 56.4% had the knowledge about the pap smear test from a healthcare professional. It was determined that academicians had lower scores from the Attitude Scale for Early Diagnosis of Cervical Cancer (88.55 +/- 9.75) and above-average scores from the Attitudes Towards Prevention of Cervical Cancer Scale (74.30 +/- 15.92). It was found that area of expertise, income status, history of infectious disease, and vaginal douching affected both the early diagnosis of cervical cancer and the attitudes towards prevention of it. Conclusion The female academicians inadequate attitudes towards early diagnosis of cervical cancer and better attitudes towards prevention. Nurses and administrators should encourage female academics and all women to screen for cervical cancer.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Medicine; Health Sciences; Surgery Medicine Sciences; Obstetrics and Gynecology; KADIN HASTALIKLARI & DOĞUM; Klinik Tıp; Klinik Tıp (MED); OBSTETRICS & GYNECOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); cancer of the cervix; gynecologic oncology; gynecology